Characterization of Mixed-Species Biofilm Formed by Vibrio parahaemolyticus and Listeria monocytogenes - Chen, Ping; Wang, Jing Jing; Hong, Bin; Tan, Ling; Yan, Jun; Zhang, Zhaohuan; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2019)
Mixed-species biofilms are the predominant form of biofilms found in nature. Research on biofilms have typically concentrated on single species biofilms and this study expands the horizon of biofilm research, where the characterization and dynamic changes of mono and mixed-species biofilms formed by the pathogens, Vibrio parahaemolyticus and Listeria monocytogenes were investigated. Compared to mono-species biofilm, the biomass, bio-volume and thickness of mixed-species biofilms were significantly lower, which were confirmed using crystal violet staining, confocal laser scanning microscopy and scanning electron microscopy. Further experimental analysis showed these variations might result from the reduction of bacterial numbers, the down-regulation of biofilm-regulated genes and loss of metabolic activity in mixed-species biofilm. In addition, V. parahaemolyticus was located primarily on the surface layers of the mixed-species biofilms thus accruing competitive advantage. This competitive advantage was evidenced in a higher V parahaemolyticus population density in the mixed-species biofilms. The adhesion to surfaces of the mixed-species biofilms were also reduced due to lower concentrations of extracellular polysaccharide and protein when the structure of the mixed-species was examined using Raman spectral analysis, phenol-sulfuric acid method and Lowry method. Furthermore, the minimum biofilm inhibitory concentration to antibiotics obviously decreased when V. parahaemolyticus co-exited with L. monocytogenes. This study firstly elucidated the interactive behavior in biofilm development of two foodborne pathogens, and future studies for biofilm control and antibiotic therapy should take into account interactions in mixed-species biofilms.